The usage of internet technology for marketing: Perspectives from local entrepreneurs of the small and medium hotel organizations in Langkawi - Mohd Yusof, Mohd Fadil (ASEAN Universities Consortium of Enterpreneurship Education (AUCEE), 2010)
Small and medium hotel organizations (SMHOs) are recognized as one of the major businesses in the tourism industry. They usually provide employment benefits to the host community, expand local economy and therefore very important to accommodate tourism demand. Taking example of SMHOs run by local entrepreneurs in Langkawi, this paper proposed that the internet is one of the most important tools for these organizations to market their products and services to a global market. It explored the perceptions of local entrepreneurs in Langkawi about utilizing the internet and analyzed the impact of this technology to their marketing strategy. This paper also highlights that internet technology provide a wide range of benefits to the entrepreneurs in terms of distributing information, establishing customers' relationship program and competing against big hotel companies. In the case of Langkawi, it was evident that the local entrepreneurs did not utilize the internet to its fullest potential and they were still adapting to this new technology as part of their marketing tool. By employing a qualitative method and using face-to-face semistructured interviews as a form of data collection, SMHOs operators were interviewed to examine the function of the internet for their organizations. The findings indicated that factors such as lack of IT's skill and limited financial resources were some of the issues that might slow down the progress of internet usage among SMHOs on the Island.